2018
DOI: 10.1039/c8ra08293f
|View full text |Cite
|
Sign up to set email alerts
|

In situ sulfuration synthesis of flexible PAN-CuS “flowering branch” heterostructures as recyclable catalysts for dye degradation

Abstract: “Flowering branch”-like PAN-CuS hierarchical heterostructures were in situ synthesized through a facile hydrothermal sulfuration growth process on PAN-based fibers prepared by electrospinning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(47 reference statements)
0
2
1
Order By: Relevance
“…0.2727 min −1 , 0.1786 min −1 , 0.1479 min −1 , 0.1300 min −1 for the samples of 4 h, 8 h, 16 h, 20 h (Figure F), respectively. Even the lowest value is much higher than the highest one (0.08 min −1 ) of the hierarchical nanocrystalline CuS with different forms in our previous work …”
Section: Resultscontrasting
confidence: 53%
“…0.2727 min −1 , 0.1786 min −1 , 0.1479 min −1 , 0.1300 min −1 for the samples of 4 h, 8 h, 16 h, 20 h (Figure F), respectively. Even the lowest value is much higher than the highest one (0.08 min −1 ) of the hierarchical nanocrystalline CuS with different forms in our previous work …”
Section: Resultscontrasting
confidence: 53%
“…For example, polyaniline (PAN)-CuS hierarchical heterostructures are synthesized in situ on PAN fibers prepared by electrospinning through a simple hydrothermal sulfuration growth process, exhibiting a "flowering branches" morphology. [71] Zhang et al synthesized flexible indium-doped tin oxide (ITO)/CuS nanosheet network films by combining the electrospinning and sputtering techniques (Figure 7e). [72]…”
Section: Electrospinning Methodsmentioning
confidence: 99%
“…For example, hierarchical 3D CuS structures have been prepared as efficient Fenton-like reagents for dye decolorization. 151,152 Our group has demonstrated that CuS nanoparticles can be decorated on the surface of electrospun PAN nanofibers via a hydrothermal reaction. 151 Owing to the small sized CuS nanoparticles, porous and freestanding characteristic of the CuS/PAN nanofibers membrane, they show a good Fenton-like property, which can catalytically degrade methylene blue (MB) in the presence of H 2 O 2 efficiently.…”
Section: Heterogeneous Chemical Catalysismentioning
confidence: 99%